2018
DOI: 10.5204/ijcjsd.v7i4.936
|View full text |Cite
|
Sign up to set email alerts
|

Sensitising Green Criminology to Procedural Environmental Justice: A Case Study of First Nation Consultation in the Canadian Oil Sands

Abstract: Procedural environmental justice refers to fairness in processes of decision-making. It recognises that environmental victimisation, while an injustice in and of itself, is usually underpinned by unjust deliberation procedures. Although green criminology tends to focus on the former—distributional dimension of environmental justice—this article draws attention to its procedural counterpart. In doing so, it demonstrates how the notions of justice-as-recognition and justice-as-participation are jointly manifeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…As discussed above, for an environmental decision-making procedure to be just, participants' perspectives and views need to be recognized; they should be given an opportunity for the provision of input toward decisions that are likely to affect their environment and to have that input respected and taken into consideration in decision-making process (George and Reed 2017;Heydon 2018). My research revealed that the ideas categorized by the opposition to farming intensification in the area were largely ignored.…”
Section: Procedural Environmental Injustice and Farming Intensificationmentioning
confidence: 94%
See 4 more Smart Citations
“…As discussed above, for an environmental decision-making procedure to be just, participants' perspectives and views need to be recognized; they should be given an opportunity for the provision of input toward decisions that are likely to affect their environment and to have that input respected and taken into consideration in decision-making process (George and Reed 2017;Heydon 2018). My research revealed that the ideas categorized by the opposition to farming intensification in the area were largely ignored.…”
Section: Procedural Environmental Injustice and Farming Intensificationmentioning
confidence: 94%
“…Much like research on distributional injustice, studies of procedural injustice have examined socially and culturally marginalized groups (Heydon 2018;Holifield 2012). Bustos and colleagues (2017) suggest, however, that explorations of procedural environmental justice should extend beyond marginalized groups and this article continues their line of thinking.…”
Section: Green Criminology and Environmental Justicementioning
confidence: 96%
See 3 more Smart Citations